Glasses and glass ceramics for medical applications - El-Meliegy, Emad; Noort, Richard van (Springer, 2012)
This book provides readers with the ability to start making their own glasses and glass-ceramics, and explores factors that control the final properties of these medical and dental materials. Also discusses current industrial challenges and their solutions